What are the cultural determinants of pro-ecological attitudes? - Matusiak, Małgorzata (W poszukiwaniu zielonego ładu, 2022)
The chapter deals with the cultural determinants of pro-ecological attitudes. It draws attention to the general regularity that care for the broadly understood natural environment is the domain of collectivist, pro-partnership, reactive and long-term-oriented cultures rather than individualistic, protransaction or linear-active cultures, focused primarily on achieving the goals of the individual, competition and maximization of the individual’s sense of happiness.